The impact of private investment on gross domestic production in srilanka - Uthayakumar, S.S.; Jesukumar, K. (University of Jaffna, 2018)
Private Sector Investment is considered as the key engine of economic growth of developed and developing countries. Empirical studies suggest that there are number factor influencing the private investment. Open Economic policies introduced in 1977 have influenced the private Investment in Sri Lanka. This research is aimed at tracing the impact of the Impact of Private Investment On Gross Domestic Function in SriLanka, by using the time series annual data for 1977-2016 in SriLanka. Multiple Regression Analysis was used to estimate the impact. Estimation method was Ordinary Least Squares(OLS).EViews 9 econometrics software were used for data analysis. The empirical evidence shows that there is a statistically significant positive impact of selected economic variables on the private investment economic growth.Further, this research has identified various problems faced In attracting private investments including ideal sector identification and the appropriate recommendations have been presented in order to realize the major benefits from the private investment in the country.
Keywords: Private Investment; Gross Domestic Production; Public Investment